2021
DOI: 10.3389/fendo.2021.794496
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy Reverses Gut Microbiome and Serum Metabolome Alterations in Premature Ovarian Insufficiency

Abstract: ObjectiveWe explored the gut microbiome and serum metabolome alterations in patients with premature ovarian insufficiency (POI) and the effects of hormone replacement therapy (HRT) with the aim to unravel the pathological mechanism underlying POI.MethodsFecal and serum samples obtained from healthy females (HC, n = 10) and patients with POI treated with (n = 10) or without (n = 10) HRT were analyzed using 16S rRNA gene sequencing and untargeted metabolomics analysis, respectively. Peripheral blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…6 Eggerthellaceae is found to promote ovarian fibrosis by increasing TGF-β levels after gavage in mice, while hormone replacement therapy reversed ovarian fibrosis induced by Eggerthellacea . 25 We found that LBP reduced the fecal abundance of Eggerthellaceae in mice. This suggests that Eggerthellaceae may be a potential target bacterium for the treatment of POI.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…6 Eggerthellaceae is found to promote ovarian fibrosis by increasing TGF-β levels after gavage in mice, while hormone replacement therapy reversed ovarian fibrosis induced by Eggerthellacea . 25 We found that LBP reduced the fecal abundance of Eggerthellaceae in mice. This suggests that Eggerthellaceae may be a potential target bacterium for the treatment of POI.…”
Section: Discussionmentioning
confidence: 68%
“…Clinical studies have shown that the structure of the gut microbiota is dysregulated in patients with POI, 6 and that the impaired gut microbiota accelerates the degeneration of ovarian function. 25 So we examined whether the ameliorative effect of LBP on POI mice was related to the gut flora. Alpha diversity is an important indicator of the richness and homogeneity of the microbial composition.…”
Section: Resultsmentioning
confidence: 99%
“…A study of 17β-estradiol hormone therapy in women with POI (n = 20 with POI [10/10 treated/not treated], n = 10 healthy controls) reported that hormone therapy partially attenuated POI-related gut microbiome dysbiosis, in that the elevated abundance of Eggerthella in POI compared with healthy women was reversed with therapy. 76 Studies of hormone therapy and the gut microbiome in naturally menopausal women are needed to determine whether hormone therapy may benefit gut health in post-menopause.…”
Section: Menopausal Hormone Therapy and The Gut Microbiomementioning
confidence: 99%
“…A further example is that of PCOS patients, in which the GM shows an abnormal Escherichia:Shigella ratio and an excess of Bacteroides compared to healthy women [ 71 ], a condition occurring also in IR and in obese women characterized by an increased Firmicutes:Bacteroidetes ratio [ 56 , 72 ]. Moreover, GM exerts a role in the pathogenesis of thyroid autoimmune disease, a frequent disorder in infertility patients [ 75 , 76 , 77 ], and a relationship between the gut microbiome and premature ovarian insufficiency (POI) has been suggested [ 78 , 79 ].…”
Section: Gut Microbiota and (In)fertilitymentioning
confidence: 99%